Language, education and Nation-building : assimilation and shift in Southeast Asia - Sercombe, Peter; Tupas, Ruanni; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This volume tracks the complex relationships between language, education and nation-building in Southeast Asia, focusing on how language policies have been used by states and governments as instruments of control, assimilation and empowerment. Leading scholars have contributed chapters each representing one of the countries in the region.
Keywords: Linguistics; Oriental literature; Languages; Language and languages; Sociolinguistics; Education; Asian Literature; Asian Languages; Education, general